Phylogenetic data suggest the reclassification of Fasciola jacksoni (Digenea: Fasciolidae) as Fascioloides jacksoni comb. nov - Heneberg, Petr (Parasitology research, 2013)
Fasciola jacksoni (Cobbold, 1869) is a highly prevalent (18-62%) species colonizing the liver (less frequently the lungs, kidneys, pericardia, and intestines) of Elephas maximus indicus and Elephas maximus maximus in the Indomalayan region, causing cirrhosis, hemorrhages, and connective tissue proliferation. The phylogenetic relationships of Fasciola jacksoni in relation to representative species of the superfamily Echinostomatoidea was assessed using four independent DNA regions. The analysis involved conserved (28S rDNA) and highly variable (ITS1, ITS2, and ND1) loci utilizing both mitochondrial (ND1) and nuclear (28S rDNA, ITS1, and ITS2) DNA. Although the analyses confirmed the monophyletic origin of the Fasciolidae family, all four analyzed regions suggested high similarity of Fasciola jacksoni to Fascioloides magna, member of a hitherto monotypic genus, parasitizing a variety of wild and domestic ruminants through the Holarctic. Supporting evidence stems also from the morphological similarities, host spectrum overlaps, and similarities in disease onset and progression. Fasciola jacksoni was reclassified to its genus in the nineteenth century by Cobbold based on the shared possession of dendriform system of gastric canals. However, Fascioloides magna (discovered later) shares this feature as well. Conversely, Fascioloides magna and Fasciola hepatica possess long median intestinal branches, whereas relatively shorter median intestinal branches are characteristic for Fasciola hepatica and Fasciola gigantica only. Both, Fascioloides magna and Fasciola hepatica, are also similar in their possession of small, but distinctive cephalic cone, while the larger one is typical for Fasciola hepatica and Fasciola gigantica. Reflecting the combined data, reclassification of Fasciola jacksoni as Fascioloides jacksoni comb. nov. is suggested.
Keywords: Elephants; mitochondriální DNA; DNA, Mitochondrial; DNA helmintů; DNA, Helminth; Cluster Analysis; fylogeneze; Sequence Analysis, DNA; Phylogeny; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; shluková analýza; sloni; mezerníky ribozomální DNA; RNA ribozomální 28S; Animals; zvířata; DNA, Ribosomal Spacer; Molecular Sequence Data; DNA, Ribosomal; RNA, Ribosomal, 28S; Fasciola